TRADISI PEMBACAAN DOA KANDUNGAN SURAT ṬĀHĀ AYAT 25-28 SEBELUM BELAJAR (Studi Living Qur’an Di Ma’had Tahfidh Al-Qur’an Al-Amien Prenduan Sumenep Madura) - Fauzi Fathur Rosi; Adrian Maulana (AL-BAYAN INSTITUTE, 2025)
Educational traditions in Islamic boarding schools (pesantren) play an important role in shaping students' character and improving the quality of learning. At Ma’had Tahfidh Al-Qur’an Al-Amien Prenduan Sumenep, there is a tradition of reciting Surah Ṭāhā verses 25–28 before starting lessons. This prayer holds deep spiritual meaning, as it is the supplication of Prophet Musa asking for openness of heart and ease in delivering knowledge, Although this practice has long been part of daily routines, it has not been widely studied academically. This research aims to explore the background and impact of the tradition on the teaching and learning process. Using a qualitative phenomenological approach, data were collected through observation, interviews, and documentation, involving caregivers, the head of the institution, class supervisors, and students as participants, The findings show that this tradition helps improve concentration, mental readiness, and strengthens the bond between teachers and students. It carries both spiritual and educational value, making it essential to preserve within Islamic academic culture.